2022
DOI: 10.1617/s11527-022-02018-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of carbonates on the formation of magnesium silicate hydrates

Abstract: The effect of carbonates on the formation of magnesium silicate hydrate phases (M-S-H) was investigated in paste experiments. At molar ratio Mg/Si = 1.5, M-S-H pastes were synthesised from silica fume and MgO or MgO/hydromagnesite in a sodium carbonate-rich environment (dissolved 1.7 g of Na2CO3 for 100 g of binder). Thermogravimetric analysis, X-ray diffraction, and 29Si MAS NMR data showed that M-S-H phases formed much faster in the presence of carbonates, which destabilised brucite. 23Na MAS NMR data, catio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 46 publications
1
28
0
Order By: Relevance
“…5. Additionally, higher Mg/Si ratios of up to 1.5, as in serpentine group minerals, can be observed in presence of carbonates [45], which were not reached otherwise, not even after a 3-yearequilibration at 20°C, or 2-year-equilibration at 50°C [41].…”
Section: Formation Of M-s-h Stability and Competition With Brucite Fo...mentioning
confidence: 96%
See 4 more Smart Citations
“…5. Additionally, higher Mg/Si ratios of up to 1.5, as in serpentine group minerals, can be observed in presence of carbonates [45], which were not reached otherwise, not even after a 3-yearequilibration at 20°C, or 2-year-equilibration at 50°C [41].…”
Section: Formation Of M-s-h Stability and Competition With Brucite Fo...mentioning
confidence: 96%
“…5. It was recently observed that dissolved carbonates also speed up the formation of M-S-H [69] by increasing the concentration of Mg due to the formation of aqueous complexes [45], as detailed in Fig. 5.…”
Section: Formation Of M-s-h Stability and Competition With Brucite Fo...mentioning
confidence: 97%
See 3 more Smart Citations

MgO‐based binders

Lothenbach,
Bernard,
German
et al. 2023
ce papers
Self Cite